2011
DOI: 10.1002/cncr.25885
|View full text |Cite
|
Sign up to set email alerts
|

Patient willingness to undergo pharmacodynamic and pharmacokinetic tests in early phase oncology trials

Abstract: BACKGROUND: Increasingly, early phase clinical trials involve pharmacodynamic (PD) and pharmacokinetic (PK) assays as well as frequent imaging studies. The authors conducted a prospective study examining patients' willingness to undergo such tests and the number of tests the patients would tolerate. METHODS: A prospective, correlative study was conducted using a self-reported questionnaire to measure patients' willingness on a scale from 1 (not willing) to 10 (very willing) to undergo various procedures (eg, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…172 Questions remain as to whether eligibility for future clinical studies should be restricted to WHO subtypes of MDS/MPN, such as a study for CMML patients alone versus broad inclusion of MDS/MPN-U patients, or whether the focus should be based on clinical disease phenotype or proliferative versus non-proliferative features. As we move forward with clinical studies based on targeted molecular pathways, these should ideally determine patient selection based upon 'founder' tyrosine kinase signaling pathway mutations or those with transcription factor mutations.…”
Section: Novel Strategies and Future Clinical Trial Designs For The Tmentioning
confidence: 99%
“…172 Questions remain as to whether eligibility for future clinical studies should be restricted to WHO subtypes of MDS/MPN, such as a study for CMML patients alone versus broad inclusion of MDS/MPN-U patients, or whether the focus should be based on clinical disease phenotype or proliferative versus non-proliferative features. As we move forward with clinical studies based on targeted molecular pathways, these should ideally determine patient selection based upon 'founder' tyrosine kinase signaling pathway mutations or those with transcription factor mutations.…”
Section: Novel Strategies and Future Clinical Trial Designs For The Tmentioning
confidence: 99%
“…Studies have demonstrated that most patients would consider research biopsies [9][10][11], suggesting that nonpatient factors might hinder biopsy accrual. One such nonpatient factor could be provider comfort level in approaching patients for biopsies.…”
Section: Introductionmentioning
confidence: 99%